14(v+2)-2v=4(3v+3)-18

Simple and best practice solution for 14(v+2)-2v=4(3v+3)-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14(v+2)-2v=4(3v+3)-18 equation:


Simplifying
14(v + 2) + -2v = 4(3v + 3) + -18

Reorder the terms:
14(2 + v) + -2v = 4(3v + 3) + -18
(2 * 14 + v * 14) + -2v = 4(3v + 3) + -18
(28 + 14v) + -2v = 4(3v + 3) + -18

Combine like terms: 14v + -2v = 12v
28 + 12v = 4(3v + 3) + -18

Reorder the terms:
28 + 12v = 4(3 + 3v) + -18
28 + 12v = (3 * 4 + 3v * 4) + -18
28 + 12v = (12 + 12v) + -18

Reorder the terms:
28 + 12v = 12 + -18 + 12v

Combine like terms: 12 + -18 = -6
28 + 12v = -6 + 12v

Add '-12v' to each side of the equation.
28 + 12v + -12v = -6 + 12v + -12v

Combine like terms: 12v + -12v = 0
28 + 0 = -6 + 12v + -12v
28 = -6 + 12v + -12v

Combine like terms: 12v + -12v = 0
28 = -6 + 0
28 = -6

Solving
28 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| x+31=-48 | | (3x-1)(2x^2+3x-3)=0 | | 9.5-23.5p=3.5(9p+3) | | (5v-6)(5+v)=0 | | 10x+6y+6+17x-16y-16= | | 4(y+3)-3=25 | | 11(z+1)-3(z-1)=3(z-2)+4(z-3) | | 9x-2(-5+7)=-8x-5 | | 4(9-14)=n-3 | | 67-5*7= | | (x+1)3=216 | | -0.04x^2+0.64x+1.94=0 | | (3x-2)(2x+6)=0 | | 9x-(8x+9)=9x-33 | | 30y+8=32 | | (2-x)(2+x)=0 | | 5=9x-8x+6 | | (7-x)(x^2+2x-3)=0 | | 6(6-4)=12y | | x+27=-52 | | x^2=128-8x | | 11x^2+2x=10 | | (7a^2-2a+6)-(-5a^2+3)=0 | | 3x+8(x-1)=0 | | -9.9-26.7=6.1-24.7r | | D^2+3d+4=0 | | 4x^2+7x+3=6 | | -9.9-26.7=6.1-24.7 | | (1.2x^5-5x^3-0.7)+(3.7x^5+3)=0 | | 2m^2-13m=0 | | 6overh=4 | | 8=6g-4 |

Equations solver categories